ASSESSMENT OF SYMPTOMS OF DYSPEPSIA SYNDROME IN NEWLY DIAGNOSED GASTRIC AND DUODENAL ULCERS, HELICOBACTER PYLORI ASSOCIATED - A. L. Korkin; S. V. Gasanova (Архивъ внутренней медицины)
In 36 residents of Khanty-Ugra with newly diagnosed gastric and duodenal ulcers evaluated the frequency of symptoms of dyspepsia syndrome and their correlation with morphological rearrangement of the gastric mucosa by the results of histological examination of biopsy samples. It was revealed that for the first time revealed ulcers manifest a combination of abdominal pain and dyspepsia in 75% of cases. This is a defining pain, verifiable in 92% of newly diagnosed cases of ulcers of the stomach and duodenum. Symptoms proper dyspeptic disorders, represented mostly by two symptoms: nausea and feeling of heaviness in the epigastric region, are more common than morphological manifestations restructuring coolant in the examined patients. The most frequent complication verified bleeding from the newly diagnosed gastric and duodenal ulcers.